2018
DOI: 10.1016/j.celrep.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Mybl2 Is Required for Proper Mesenchymal-to-Epithelial Transition during Somatic Reprogramming

Abstract: SummaryDuring somatic reprogramming, Yamanaka’s pioneer factors regulate a complex sequence of molecular events leading to the activation of a network of pluripotency factors, ultimately resulting in the acquisition and maintenance of a pluripotent state. Here, we show that, contrary to the pluripotency factors studied so far, overexpression of Mybl2 inhibits somatic reprogramming. Our results demonstrate that Mybl2 levels are crucial to the dynamics of the reprogramming process. Mybl2 overexpression changes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
0
16
2
Order By: Relevance
“…Our study has revealed a spontaneous time-dependent conversion from human skin FBs into a functional KCs phenotype in vitro. Such conversion was significantly different from the previous studies 37. The global morphological change from FBs to KLCs was observed on day 90 in the primary culture.…”
Section: Discussioncontrasting
confidence: 98%
“…Our study has revealed a spontaneous time-dependent conversion from human skin FBs into a functional KCs phenotype in vitro. Such conversion was significantly different from the previous studies 37. The global morphological change from FBs to KLCs was observed on day 90 in the primary culture.…”
Section: Discussioncontrasting
confidence: 98%
“…3c). These factors have all been previously implicated in the EMT, but are not typically considered canonical EMT regulators [29][30][31][32][33][34] . To assess the accuracy of these results, we used ATAC-seq to assess the accessibility of transcription factor motifs throughout the EMT and compared accessibility dynamics to the inferred regulon activity.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of HMGN nucleosome‐binding proteins enhances the kinetics of iPSCs formation by accelerating the closing of MEF‐specific open chromatin, while the differentiation potential of iPSCs is unaffected (He et al , 2018), suggesting that HMGNs function to stabilize cell fate rather than determining cell identity. Mybl2 is a somatic cell gatekeeper that inhibits the opening of chromatin to activate MET genes in the early stage of reprogramming (Ward et al , 2018). Mbd3 maintains the somatic cell fate and depletion of Mbd3 strongly promotes MEF reprogramming to iPSCs (Luo et al , 2013; Rais et al , 2013).…”
Section: Introductionmentioning
confidence: 99%